2019
DOI: 10.1007/s00467-019-04316-5
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant organisms in urinary tract infections in children

Abstract: The global spread of multidrug-resistant organisms has led to an increase in urinary tract infections (UTIs) in children that are difficult to treat. This review explores the current literature regarding multidrug-resistant UTIs in childhood and proposes an approach to management. Multidrug-resistant organisms include a wide range of potential urinary tract pathogens and, while most literature on drug resistance in UTIs during childhood has focused on extended-spectrum beta-lactamase producing organisms, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 63 publications
1
30
0
3
Order By: Relevance
“…These findings may be associated with the significant rise of AMC resistance. Since resistance is generally mediated by a plasmid encoding resistance to several antimicrobials, this could explain our findings, as previously documented in ESBL-producing bacteria [ 22 ].…”
Section: Discussionsupporting
confidence: 77%
“…These findings may be associated with the significant rise of AMC resistance. Since resistance is generally mediated by a plasmid encoding resistance to several antimicrobials, this could explain our findings, as previously documented in ESBL-producing bacteria [ 22 ].…”
Section: Discussionsupporting
confidence: 77%
“…The higher prevalence of MDR in Kathmandu than Bhaktapur may be due to bigger general hospitals in Kathmandu, where children and adults with more risk factors for MDR are treated, than in Bhaktapur. Previous antimicrobial use, previous hospitalisation, urinary catheterisation, and urinary tract anomalies are some of the known risk factors for MDR [19,20]. We found that MDR was significantly more prevalent in children younger than 5 years than older children.…”
Section: Discussionmentioning
confidence: 62%
“…In Turkey, comparing the data collected in a single paediatric institution from 2009 to 2014, it was shown that E. coli resistance during the study period increased for ampicillin from 47.1% to 89%, for trimethoprim-sulphamethoxazole from 44.8% to 56% and for nitrofurantoin from 5.3% to 15.1% [8]. The most frequent risk factors associated with the development of UTIs due to antimicrobial-resistant pathogens are the previous use of antibiotics and urinary tract abnormalities [7][8][9][10]. Nevertheless, data for the surveillance of antibiotic resistance in UTIs frequently do not distinguish between adult and paediatric populations, and in many cases, the data are limited to single resistance mechanisms of specific pathogens, predominantly extended-spectrum beta-lactamase (ESBL)producing E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, data for the surveillance of antibiotic resistance in UTIs frequently do not distinguish between adult and paediatric populations, and in many cases, the data are limited to single resistance mechanisms of specific pathogens, predominantly extended-spectrum beta-lactamase (ESBL)producing E. coli. Furthermore, the prevalence of ESBL-producing pathogens in paediatric UTIs varies from 0.5% to 50% across studies [9][10][11]. In light of the variability in the data in the literature, it is necessary to conduct surveillance studies to determine the prevalence of antibiotic resistance in paediatric UTIs in specific geographical areas to optimize therapeutic management.…”
Section: Introductionmentioning
confidence: 99%